Steel Structural Building by using Pushover Analysis (Journal of Civil Engineering Researchers, 2017)
In this paper, performance level of steel moment resisting frame building has been assessed by pushover analysis. This journal aims to study the strength of the proposed building in the inelastic region. The proposed building is the regular shaped four-story steel structure which is situated in seismic zone Ⅱ. Its height is 12.80 m above the ground level. The structure is composed of steel moment resisting frame and it is designed out by SAP-2000 Version 18 software. The result shows that, the strength of the structure which reaches safety in static analysis also maintain for the safety of life when its structure runs in the inelastic static analysis until it gets target displacement. There are 408 hinges in the building to present the capacity curve and performance level. And also, it can get the knowledge of FEMA-356 usage in pushover analysis
Keywords: Seismic zone; Pushover Analysis; SAP 2000; FEMA_356